2021
DOI: 10.12998/wjcc.v9.i28.8295
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, nutritional deficiencies, and schizophrenia: An association worthy of constant reassessment

Abstract: Schizophrenia is a mental health disorder that occurs worldwide, cutting across cultures, socioeconomic groups, and geographical barriers. Understanding the details of the neurochemical basis of schizophrenia, factors that contribute to it and possible measures for intervention are areas of ongoing research. However, what has become more evident is the fact that in targeting the neurochemical imbalances that may underlie schizophrenia, the type of response seen with currently available phamacotherapeutic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 137 publications
(166 reference statements)
0
16
0
Order By: Relevance
“…No significant association was found, which points to a more complex pathogenesis. Nevertheless, nutrition is most altered in patients with schizophrenia even relative to other psychiatric disorders, 45 which suggests a possible influence on the microbiome and subsequently on TMA and butyric acid levels through a disturbed diet.…”
Section: Discussionmentioning
confidence: 99%
“…No significant association was found, which points to a more complex pathogenesis. Nevertheless, nutrition is most altered in patients with schizophrenia even relative to other psychiatric disorders, 45 which suggests a possible influence on the microbiome and subsequently on TMA and butyric acid levels through a disturbed diet.…”
Section: Discussionmentioning
confidence: 99%
“…Sch is one of the most common mental disorders that affects the working population in many countries; although, incidence rates range from 0.2% in some African countries (Central African Republic, Somalia) to 0.5% in the USA, Australia and New Zealand [ 111 ]. Although some of the differences in these epidemiological rates may be due to different approaches and timing of the diagnosis of this mental disorder, differences in the prevalence of Sch can also be explained by studies that demonstrate that the lack of certain nutrients in the diet can contribute to the development of Sch as an additional externally modifiable risk factor [ 112 , 113 ]. Notably, some authors have shown that deficiencies in essential vitamins, minerals and polyunsaturated fatty acids are often reported in the population, but rarely in patients with Sch [ 114 , 115 , 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested the link between diet and mental health [4][5][6]. Depression has been associated with unhealthy lifestyles, including alcohol drinking and poor dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…SSDs have been associated with a higher prevalence of depression and anxiety [ 10 ]. In addition, high sugar intake has also been reported in patients with schizophrenia and can predict the severity of schizophrenia symptoms [ 6 ]. Therefore, reduction or abstinence from sugar-containing drinks may be an appropriate public health strategy not only to support those aiming to achieve healthy body weight [ 11 ] but also to reduce the risk or severity of depression and anxiety, and schizophrenia symptoms in psychiatric patients.…”
Section: Introductionmentioning
confidence: 99%